'A Democracy That Will Know Not the Differences of Race': American 'Globetrotting' in South Africa from the 1920s through the 1980s in Perspective. Issue 8 (15th July 2022) - Dyreson, Mark; Sikes, Michelle M.
ABSTRACT: When in 1931 the United States sent an all-white track and field team to compete against an all-white South African roster, it inaugurated a series of interchanges that over the next six decades illuminated intersections between politics, race, and sport in both nations. Between the 1930s and the 1980s, these periodic sporting encounters served as lightning rods that rallied civil rights activists and anti-apartheid protestors, linking battles over sport and race in both nations. By the 1960s, as legal segregation in the US eroded while the system in South Africa hardened, titans of American sporting desegregation who championed athletes' rights such as Jack Robinson linked their endeavours to anti-apartheid campaigns. At the end of the 1980s, two multi-racial groups of American athletes broke international anti-apartheid bans and created a new debate over the concept of athletes' rights. As apartheid crumbled in the early 1990s, an American legal scholar sought to codify this new perspective into a federal 'athletes' bill of rights', providing a paradoxical postscript for this special issue on 'Excavating the Ancestry of "Globetrotting": New Perspectives on the Intersection of Racial Politics, Civil Rights Struggles and Anti-Apartheid Crusades in US Track and Field from the 1920s through the 1980s'.